Complicated femoral hernia: Minimally invasive surgery management - Deepa Kizhakke Veetil; Randeep Wadhawan; Naveen Kumar Verma; Shamsu Rehman Tanai (Journal of Minimal Access Surgery, 2023)
Introduction: Complicated femoral hernias can be managed by minimally invasive surgery techniques in the select group of patients. This helps reduce the morbidity of open surgery and enables faster recovery of the patient. Concerns Addressed: Delay in diagnosis can be reduced by a good clinical examination of the patient with a high index of suspicion for these patients. Imaging helps to confirm the clinical diagnosis and plan the operative intervention. In trained hands, the complicated femoral hernias can be managed by laparoscopy which enables better visualisation. Post-operative recovery is also enabled by the minimally invasive surgery done. Conclusion: Minimally invasive laparoscopic surgery can be done in the select group of cases of complicated femoral hernia by trained surgeons.